IMF Research Perspective : Fall 21/Winter 22. (IMF Research Perspectives; IMF Research Perspectives ;, 2022)
This issue of the IMF Research Perspective looks at the inter-connectedness of the world economic system and how diverse shocks can affect global supply chains. The articles in this issue track the way COVID-19 triggered disruptions in the supply chain and explains why trade networks are so difficult to disentangle. However, the pandemic is not the only event affecting global supply chains; cross-border spillovers of technology wars and natural disasters are other factors to consider. The overarching message from these articles is clear: there is a need for international cooperation to deal with the consequences of these shocks-whether it is ending the COVID-19 pandemic or mitigating climate change.